Competency of workers in building control department of local authorities / Suhirman Mohammad - Mohammad, Suhirman (2002)
Construction is the most important industry that contributes towards development of our nation. Physically all the effort should be provided in order to cater for the best quality of buildings being constructed. Construction plays a major role to assure the realisation of citizen’s aspiration towards development of Malaysia. Construction was the most important proofs to be referred as a measurement of the effort of our nation. Looking at our construction industry we can see that the developments of the buildings were depends on the handling of the projects. The best quality buildings can only be built well if regulatory body did well during projects approvals. Regularly, when talking about construction project located within certain area, we will noticed that they have to deal with Local Authorities of particular territory of authorization. Then, the developments of constructional projects were bound to regulation^, and conditions applied to the territory. Local Authority, which is mainly the government body which hold the obligation of authorization for the developments of constructional projects in their respective area. We always heard rumours saying that government’s servant are not competent in handling their duties obligated for them. Due to those consequences, I realized that something somehow should be done to reveal the reality behind that rumours. The lack of competencies among governments’ staff was happened continuously long ago. On realizing that situation, writer feels that something had to be done to reveal the reasons behind the scenario. Should there be good reasons to explain on the government servants’ attitude. Writer has made decision to write about the real situation at Local Authority. Specifically, writers will go deep under to seek information from the Building Control Department and Building Department…